2019
DOI: 10.3390/ijms20194731
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Monocyte and T Cell Cytokine Profiles in Autism Spectrum Disorders: Effects of Dysregulated Innate Immune Responses on Adaptive Responses to Recall Antigens in a Subset of ASD Children

Abstract: Changes in monocyte cytokine production with toll like receptor (TLR) agonists in subjects with autism spectrum disorders (ASD) were best reflected by the IL-1β/IL-10 ratios in our previous research. The IL-1β/IL-10 based subgrouping (low, normal, and high) of ASD samples revealed marked differences in microRNA expression, and mitochondrial respiration. However, it is unknown whether the IL-1β/IL-10 ratio based subgrouping is associated with changes in T cell cytokine profiles or monocyte cytokine profiles wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Therefore, we decided to assess changes of monocyte cytokine parameters in association with co-morbid conditions frequently found in ASD subjects. We found GI symptoms along with NFA or FPIES like conditions in ASD subjects at high frequency (>60%), which was consistent to our previous studies [10,12,29]. Most of the ASD patients with GI symptoms had a history of FPIES like symptoms ( Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, we decided to assess changes of monocyte cytokine parameters in association with co-morbid conditions frequently found in ASD subjects. We found GI symptoms along with NFA or FPIES like conditions in ASD subjects at high frequency (>60%), which was consistent to our previous studies [10,12,29]. Most of the ASD patients with GI symptoms had a history of FPIES like symptoms ( Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…IIM is closely associated with changes in monocyte cytokine profiles [16]. Previously, we have found significant changes in monocyte cytokine profiles in a subset of ASD patients [10,11]. Therefore, this study addressed whether the specific monocyte cytokine parameters are associated with ASD co-morbid conditions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ELISA reagents were obtained from BD Biosciences (San Diego, CA, USA) and R & D (Minneapolis, MN, USA). PBMo were incubated overnight with and without stimuli of innate immunity [lipopolysaccharide (LPS) (0.1 μg/ml, GIBCO-BRL, Gaithersburg, MD, USA), zymosan (50 μg/ml, Sigma-Aldrich, St. Luis, Mo, USA), CL097 (20 μM, Invivogen, San Diego, CA, USA), and candida heat extract (HCKA, 10 7 cells/ml, Invivogen, as a source of ß-glucan) in the same culture conditions detailed previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the periphery, increased expression of pro-in ammatory cytokines, including interleukin-1 beta (IL-1β), IL-6, tumor necrosis factor alpha (TNF-α), transforming growth factor beta, IL-8, and IL-17 has been observed in the plasma, serum, and peripheral blood mononuclear cells (PBMCs) of patients with ASD (7,8). Antioxidant networks (e.g., superoxidase dismutase expression and activity) and the responses to innate immunity stimuli (e.g., lipopolysaccharide and zymosan) have been found to be dysregulated in the monocytes of ASD patients (9)(10)(11). In the central nervous system (CNS), a positron emission tomography study and a few postmortem studies have shown microglial activation in the brains of ASD patients (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%